Associations among serum markers of inflammation, life stress and suicide risk in patients with major depressive disorder. (October 2020) - Su, Yun-Ai; Lin, Jing-Yu; Liu, Qi; Lv, Xiao-Zhen; Wang, Gang; Wei, Jing; Zhu, Gang; Chen, Qiao-Ling; Tian, Hong-Jun; Zhang, Ke-Rang; Wang, Xue-Yi; Zhang, Nan; et al.
Abstract: Background: Patients with major depressive disorder (MDD) are at high risk for suicide. As the worst outcome of MDD and common self-concealment in patients with suicide risk, studies of biomarkers may provide useful tools for suicide prevention and treatment. Methods: This study recruited 168 patients with MDD from the Objective Diagnostic Markers and Personalized Intervention in MDD patients (ODMPIM), including 50 patients with suicide risk. Based on previous evidence and hypothesis, 23 targeted serum biomarkers involving immune-inflammation, neurotrophins, hypothalamic–pituitary–adrenal (HPA) axis and metabolism, were measured. We used path analysis and principal components analysis (PCA) to clarify the associations among serum biomarkers, childhood adversities, adulthood life events, severity of depression and suicide risk. Results: We identified that patients with suicide risk had a higher level of inflammatory markers in serum than patients without suicide risk ( P < 0.001), especially chemokine (C-X-C motif) ligand 1 (CXCL-1). After using the Bonferroni correction, there were no differences in biomarkers related to neurotrophins, HPA-axis and metabolism. In addition, a higher proportion of patients with suicide risk had adulthood adversity (assessed by Life Events Scale) ( P = 0.003). Intriguingly, path analysis demonstrated that the association between adulthood adversity and suicide risk mainly depended on severity of depression and inflammatory index. Conclusion: This study highlights the possible role of inflammation involved in suicide risk of MDD patients. Inflammatory markers have the potential for early identification and then reducing suicidal behaviors or becoming novel treatment targets in suicide risk management. Highlights: Adulthood adversity was associated with suicide risk in MDD patients. Patients with suicide risk had higher level of inflammatory markers. The association between adulthood adversity and suicide risk partly depended on inflammatory activation.